Volledige werken van Theodoor Van Ryswyck : met levensbericht van den dichter - Staes, J.; Van Ryswyck, Theodoor (Antwerpen : Lodewijk Janssens, 1884)
Bibliotheek E. Anseele
Aanwezig : 3 delen.
Nederlands
Meerdelige publicatie
Keywords: literatuur